Loki : a bad God's guide to taking the blame - Stowell, Louie (Somerville, Mass. : Walker Books, 2022)
"When Heimdall and Hyrrokkin abandon their 'children' to go on holiday, Odin sends Baldur - Thor's half brother and god of making Loki look bad - to babysit. As Baldur and Thor bond, Loki's attempts to prove he's good start getting a bit desperate. After the drama teacher casts him as the villain in the school play, Loki starts to wonder whether there's any point in being good when everyone seems convinced of his villainy. That is until he discovers a rather unusual ring among the costumes and props. A ring that looks suspiciously like the cursed ring of Andvari, one that promises Loki the world if only he gives in to his deepest, darkest desires . . . "--Amazon.
5-8
English.
Keywords: Loki -- (Norse deity) -- Juvenile fiction; Thor -- (Norse deity) -- Juvenile fiction; Loki -- (Norse deity) -- Fiction; Thor -- (Norse deity) -- Fiction; Loki -- (Norse deity) -- Fiction; Thor -- (Norse deity) -- Fiction; Conduct of life -- Juvenile fiction; Diaries -- Juvenile fiction; Gods, Norse -- Juvenile fiction; Middle school students -- Juvenile fiction; Conduct of life -- Fiction; Diaries -- Fiction; Gods, Norse -- Fiction; Middle school students -- Fiction; Conduct of life -- Fiction; Diaries -- Fiction; Gods and goddesses -- Fiction; Middle school students -- Fiction; Diary fiction